High‐Speed Preparation of <111>‐ and <110>‐Oriented β‐SiC Films by Laser Chemical Vapor Deposition. Issue 3 (14th December 2013) - Zhang, Song; Xu, Qingfang; Tu, Rong; Goto, Takashi; Zhang, Lianmeng; Besmann, T.
<x xml:space="preserve">Abstract</x> Highly oriented <111> and <110> β‐SiC films were prepared on Si(100) single crystal substrates by laser chemical vapor deposition using a diode laser (wavelength = 808 nm) and HMDS (Si(CH3)3–Si(CH3)3) as a precursor. The effects of laser power (PL), total pressure (Ptot), and deposition temperature (Tdep) on the orientation, microstructure, and deposition rate (Rdep) were investigated. The orientation of the β‐SiC films changed from <111> to random to <110> with increasing PL and Ptot. The <111>‐, randomly, and <110>‐oriented β‐SiC films exhibited dense, cauliflower‐like, and cone‐like microstructures, respectively. Stacking faults were observed in the <111>‐ and <110>‐oriented films, and aligned parallel to the (111) plane in the <111>‐oriented film, whereas they were perpendicular to the (110) plane in the <110>‐oriented film. The highest Rdep of the <111>‐oriented β‐SiC film was 200 μm/h at Ptot = 200 Pa and Tdep = 1420 K, whereas that of the <110>‐oriented film was 3600 μm/h at Ptot = 600 Pa and Tdep = 1605 K.